Comparative analyses of plasma probe diagnostics techniques - Godyak, V. A.; Alexandrovich, B. M. (Journal of applied physics, 2015)
The subject of this paper is a comparative analysis of the plasma parameters inferred from the classical Langmuir probe procedure, from different theories of the ion current to the probe, and from measured electron energy distribution function (EEDF) obtained by double differentiation of the probe characteristic. We concluded that the plasma parameters inferred from the classical Langmuir procedure can be subjected to significant inaccuracy due to the non-Maxwellian EEDF, uncertainty of locating the plasma potential, and the arbitrariness of the ion current approximation. The plasma densities derived from the ion part of the probe characteristics diverge by as much as an order of magnitude from the density calculated according to Langmuir procedure or calculated as corresponding integral of the measured EEDF. The electron temperature extracted from the ion part is always subjected to uncertainty. Such inaccuracy is attributed to modification of the EEDF for fast electrons due to inelastic electron collisions, and to deficiencies in the existing ion current theories; i.e., unrealistic assumptions about Maxwellian EEDFs, underestimation of the ion collisions and the ion ambipolar drift, and discounting deformation of the one-dimensional structure of the region perturbed by the probe. We concluded that EEDF measurement is the single reliable probe diagnostics for the basic research and industrial applications of highly non-equilibrium gas discharge plasmas. Examples of EEDF measurements point up importance of examining the probe current derivatives in real time and reiterate significance of the equipment technical characteristics, such as high energy resolution and wide dynamic range.